2014
DOI: 10.1167/iovs.14-14023
|View full text |Cite
|
Sign up to set email alerts
|

Serine Proteinase Inhibitor SERPINA3K Suppresses Corneal Neovascularization Via Inhibiting Wnt Signaling and VEGF

Abstract: Purpose: To evaluate the anti-neovascularization effects and investigate the possible mechanisms of SERPINA3K, a member of serine proteinase inhibitor family, using a specific rat model of suture-induced corneal neovascularization. Methods: A rat corneal suture model was set up and SERPINA3K was topically administered three times daily for 7 days. The clinical indications were evaluated on day 2, 5 and 7, including area of neovascularization and inflammation index. The eyeballs were collected after day 7 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…We demonstrated that corneal suture can induce corneal neovascularization and inflammation and proved that the corneal suture can be used as a good and specific model for corneal neovascularization. 15 In addition, we also showed that corneal suture increased levels of VEGF and key factors of the Wnt pathway, such as b-catenin. 15 In this present study, we expanded on the preceding by investigating the role of miR-184 in corneal neovascularization using the same corneal suture model, and we also performed transfection of mimics and iovs.arvojournals.org j ISSN: 1552-5783 inhibitor of miR-184 in cultured cells to further illustrate the underlying mechanisms.…”
mentioning
confidence: 68%
See 4 more Smart Citations
“…We demonstrated that corneal suture can induce corneal neovascularization and inflammation and proved that the corneal suture can be used as a good and specific model for corneal neovascularization. 15 In addition, we also showed that corneal suture increased levels of VEGF and key factors of the Wnt pathway, such as b-catenin. 15 In this present study, we expanded on the preceding by investigating the role of miR-184 in corneal neovascularization using the same corneal suture model, and we also performed transfection of mimics and iovs.arvojournals.org j ISSN: 1552-5783 inhibitor of miR-184 in cultured cells to further illustrate the underlying mechanisms.…”
mentioning
confidence: 68%
“…The rat corneal suture procedure was described previously. 15 Briefly, after induction of general anesthesia by intraperitoneal injection with pentobarbital (40-50 mg/kg), topical application of 0.5% proparacaine ophthalmic solution was added. Three corneal sutures (10-0 nylon) were conducted in the cornea between corneal center and the limbus at the 12, 4, and 8 o'clock positions.…”
Section: Corneal Suture Modelmentioning
confidence: 99%
See 3 more Smart Citations